Techno-Economic and Environmental Assesment of Compressor Retrofitting Procedure - Orhan Ekren (Journal of Advanced Thermal Science Research, 2015)
In this study, retrofitting of a fixed speed refrigeration system to a variable speed refrigeration system is investigated. Economical and technical benefits of the retrofitting procedure are also studied. Refrigeration systems are usually designed to overcome maximum load conditions. However, they work under partial load in most of their life cycle. Hence, in this study a variable speed compressor that equalizes the cooling load to the demand that assures significant energy saving is considered. As a result of this study, the retrofitted variable speed compressor performed 17% decreased energy consumption versus the thermostatic controlled fixed speed system. Also, the retrofitting procedure provided considerable payback time. From the result, 10750 kilograms less carbon emission per year as an environmental benefit within retrofitting procedure is obtained.